The New Woman Redefined: Constructing Gender Through Sports - Anderson, Patricia (2007)
The economic, cultural, and political transformations of the early twentieth century created the foundation for the re-evaluation of gender and a redefinition of the meanings of masculinity and femininity. Over the first four decades, a new model of womanhood emerged in Argentina, swiftly replacing previous gender representations. Amongst the numerous factors that gave new meanings to womanhood and femininity, the rise of female sports and deportismo had a major, yet thus far unexamined, role. Deportismo, as a physical practice strongly grounded on a moral discourse, generated new ways of thinking about and perceiving the relationship between the mind and the body. The connections and intersections between its core aspects -moral development and physical enhancementaffected the way femininity was experienced and constructed. The gradual growth of female sports and physical activity disproved traditional assumptions about the nature of the female body and the essence of the female mind, and the multiple ways in which they interacted to create femininity. Women who had access to a sporting life developed physical abilities and moral -or spiritual- qualities that confronted long-established definitions of womanhood. The strong, agile, and powerful sporting women who deftly exhibited their bodies demolished the representation of the fragile, weak, and uncontrolled female body that had prevailed throughout the nineteenth century. Deportismo, circumscribed by a strong moral discourse, also helped to develop emotional and psychological qualities, contributing to create assertive, confident, and spiritually strong women. In addition to its physical and emotional impact, the practice of sports had a profound effect on women’s lifestyle, transforming their leisure, affecting the way they dressed and behaved, and influencing the manner in which they interacted socially by reshaping their networks of acquaintances. These changes generated many fears and uncertainties, particularly with the popularization of deportismo that occurred after the twenties. Sporting women confronted a variety of accusations from journalists, intellectuals, sporting enthusiasts, and other “experts” who saw these changes as a threat to the gender order. An examination of the rise of female deportismo, its effects on women, and the reactions it generated provides a deeper understanding of gender dynamics in early twentieth-century Argentina.